Vt publicitário para redes sociais: skateboardingem ação - (:unkn) unknown (Universidade Federal do Pampa, 2020)
This work was carried out from the theme “Advertising VT's on social networks”, which aims to analyze the specifics of audiovisual productions of advertising VT's of skateboarding sport brands, on the Instagram social network, evaluating the way these products take on the platform. IGTV video Through the choice of VT's, the analysis of Hondar Skateboarding and Nomad Skateboarding's Instagram production techniques was started, using the description method that allows us to discover variables in this production that happen in IGTV through the decoupalgem of the videos, and the observation method. A systematic approach will describe which phenomena resemble or differ from other social networks. Reaching the following question: Does audiovisual advertising production for Instagram differ in what respects from other platforms? And through elements analyzed and observed it was possible to find factors that differ these productions from other platforms.
Keywords: Vídeos para Internet; Recursos audiovisuais; Gravações de vídeo - Produção e direção; Redes sociais on-line; Audiovisual resources; Online social networks; CNPQ::CIENCIAS SOCIAIS APLICADAS